Performance Analysis of Different Electrical Filters in 10G Hybrid Passive Optical Network - Subhashini, N.; Brintha Therese, A. (International Journal of Engineering and Technology, 2018)
With growing number of applications and network traffic, optic fibers are extensively used in the access part of the network. Passive Optical Networks (PON) in particular, Ethernet PON (EPON) networks based on Time Division Multiple Access (TDMA) are more prominently used in many parts of the world. Though Wavelength Division Multiplexing (WDM) PON has its own advantages, considering the cost and utilisation of such networks in the access part makes it less useful. On the other hand, Hybrid PON network combines the advantages of both EPON and WDM PON Networks. The objective of this paper is to identify suitable electrical filters for a 16-channel Hybrid Passive Optical Network with a transmission rate of 10Gbps per channel, by analysing their performance in terms of Q factor and Bit Error Rate. Different filters like the Bessel filter, Gaussian filter, Raised Cosine Filter, Rectangular filter, Butterworth filter, Chebyshev Filter are compared and their performances are evaluated. DB Modulation format that provides a longer reach is used at the transmitter to evaluate the different scenarios and the simulation is carried out using Optisystem.